New insights on taxonomy, phylogeny and population genetics of Leishmania (Viannia) parasites based on multilocus sequence analysis. - Mariana C Boité; Isabel L Mauricio; Michael A Miles; Elisa Cupolillo (Public Library of Science (PLoS), 2012)
The Leishmania genus comprises up to 35 species, some with status still under discussion. The multilocus sequence typing (MLST)--extensively used for bacteria--has been proposed for pathogenic trypanosomatids. For Leishmania, however, a detailed analysis and revision on the taxonomy is still required. We have partially sequenced four housekeeping genes--glucose-6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6PGD), mannose phosphate isomerase (MPI) and isocitrate dehydrogenase (ICD)--from 96 Leishmania (Viannia) strains and assessed their discriminatory typing capacity. The fragments had different degrees of diversity, and are thus suitable to be used in combination for intra- and inter-specific inferences. Species-specific single nucleotide polymorphisms were detected, but not for all species; ambiguous sites indicating heterozygosis were observed, as well as the putative homozygous donor. A large number of haplotypes were detected for each marker; for 6PGD a possible ancestral allele for L. (Viannia) was found. Maximum parsimony-based haplotype networks were built. Strains of different species, as identified by multilocus enzyme electrophoresis (MLEE), formed separated clusters in each network, with exceptions. NeighborNet of concatenated sequences confirmed species-specific clusters, suggesting recombination occurring in L. braziliensis and L. guyanensis. Phylogenetic analysis indicates L. lainsoni and L. naiffi as the most divergent species and does not support L. shawi as a distinct species, placing it in the L. guyanensis cluster. BURST analysis resulted in six clonal complexes (CC), corresponding to distinct species. The L. braziliensis strains evaluated correspond to one widely geographically distributed CC and another restricted to one endemic area. This study demonstrates the value of systematic multilocus sequence analysis (MLSA) for determining intra- and inter-species relationships and presents an approach to validate the species status of some entities. Furthermore, it contributes to the phylogeny of L. (Viannia) and might be helpful for epidemiological and population genetics analysis based on haplotype/diplotype determinations and inferences.